The Influence of Transparency and Trust on Parental Participation in MTS Negeri Cakung District, East Jakarta - Zamarotul Azkiyah; Nurhattati Fuad; Matin Matin (Universitas Negeri Malang, 2026)
Abstract: This study examines the influence of transparency and trust on parental participation in MTS Negeri Kecamatan Cakung, Jakarta Timur. Using a quantitative correlational design, data were collected from 120 parents selected through proportionate stratified random sampling. The primary data collection tool was a structured questionnaire measuring transparency, trust, and parental participation. Descriptive analysis revealed that trust scored higher (M = 4.37, SD = 0.46) than transparency (M = 4.23, SD = 0.54) and parental participation (M = 3.89, SD = 0.61). Correlation analysis showed significant positive relationships among transparency, trust, and parental participation, with trust emerging as a stronger predictor. Regression analysis confirmed that transparency (β=0.32, β=0.32, p < 0.01) and trust (β=0.41, β=0.41, p < 0.001) significantly influence parental participation, collectively explaining 42% of the variance (R2=0.42, R2=0.42). Furthermore, trust was found to moderate the impact of transparency on parental participation. These findings highlight the need for schools to adopt integrated strategies that promote transparent communication and build trust with parents. The study provides practical implications for school leaders, policymakers, and educators to enhance parental engagement, ultimately contributing to better educational outcomes. Future research is encouraged to explore the influence of cultural, socioeconomic, and policy-related factors on school-community partnerships. Keywords: transparency, trust, parental participation, educational engagement, school-community partnerships.